Dayah Strategy of Aceh in Preparing For Professional Advisory in Bireuen District - Muhibuddin Muhibuddin; Muntasir Muntasir; Muhammad Aminullah; Hasbullah Hasbullah; Putra Saida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Muhadharah activities that have existed and become part of beut in these three dayahs, enabled the birth of teungku dayah who were ready to appear in society as competent dā‘is. In fact, not all teungku dayah are able to appear as dā‘i figures that are referred to by society. This research is a qualitative descriptive study which obtained data by conducting interviews, observations and document review of social conditions at the study site. Furthermore, the data obtained were analyzed and came to a conclusion that the implementation of muhadharah on the salafi dayah in Bireuen Regency was generally carried out by following the old tradition and still accommodating and adopting the development and dynamics of today's muhadharah, such as language, tools and material mastery. In order to realize the effectiveness of the implementation of muhadharah on the salafi dayah the ulama and the dayah leaders argued that the muhadharah should receive serious attention in the form of its vision and mission.